CHALLENGES OF TECHNICAL TRANSLATION IN ENGLISH LESSONS FOR STUDENTS OF TECHNICAL SPECIALTIES (Web of Teachers: Inderscience Research, 2024)
Technical translation is a vital component of English language education for students specializing in technical fields. This paper explores the unique challenges associated with technical translation, such as complex terminology, cultural differences, and the necessity for precision and clarity. It examines how these challenges impact students' learning processes and offers strategies for educators to improve the teaching of technical translation. The study emphasizes the importance of integrating translation skills into technical curricula to better prepare students for global communication and professional demands.